Pt Hollow Nanospheres as an Electrocatalyst for the Oxygen Reduction Reaction. (7th July 2017) - Fang, Baizeng; Bonakdarpour, Arman; Pinaud, Blaise A; Wilkinson, David P
Abstract : Pt hollow nanospheres (HNSs) were deposited uniformly on commercial Vulcan XC-72R (VC) and explored as an electrocatalyst for the oxygen reduction reaction (ORR) in PEMFCs. VC-supported Pt HNSs have a uniform Pt HNS particle size of ca. 18 nm and a homogeneous particle distribution on the support. The Pt HNSs consist of discrete Pt nanoparticles (NPs) with a crystallite size of ca. 2-3 nm. Compared with its counterpart Pt(20 wt%)NP/VC the as-synthesized Pt(20 wt%)HNS/VC has demonstrated a considerable enhancement in the mass activity towards the ORR because of its unique nanostructure and the contribution from alloying of Pt with Co.